Accelerated stability testing and simulated gastrointestinal release of encapsulated betacyanins and phenolic compounds from Bougainvillea glabra bracts extract. (1st November 2022) - Kuhn, Fernanda; Santos Dorneles, Mariane; Pelayo Zapata Noreña, Caciano
Highlights: B. glabra powders were produced by freeze drying using polydextrose and inulin. Betacyanins and phenolics from Bougainvillea glabra powders showed high stability. In vitro digestion showed the highest betacyanins release in the gastric phase. Betacyanins and phenolics release was slower in the powders containing inulin. Interactions among fiber and bioactive compounds may prevent its premature release. Abstract: Bougainvillea glabra bracts extract was encapsulated by freeze drying using the prebiotic fibers polydextrose and inulin as encapsulating materials. The stability and the in vitro gastrointestinal digestion of B. glabra powders were evaluated. High retentions of betacyanins (77–86%) were obtained at 30 °C after 42 days of storage. At 50 °C, took place the highest betacyanins degradation, resulting in retentions ranging from 50 to 64% in the powders containing inulin and polydextrose, respectively. Total phenolic compounds had a final retention of 49–59% and antioxidant capacity varied from 45 to 53% at 50 °C. The betacyanins degradation followed the first-order kinetic and the degradation rates ranged from 0.0030 to 0.0163 days −1 . The simulation of gastrointestinal digestion showed a maximum release and stability of betacyanins and phenolics in the gastric phase; however the release was slower in the powders containing inulin. The powders showed great potential as bioactive ingredients in foods.